EFFECTS OF DIFFERENT TYPES AND RATES OF BIOCHAR SUBSTRATES ON GROWTH PERFORMANCES AND YIELD OF KAEMPFERIA PARVIFLORA WALL. EX. BAKER GROWN ON SOILLESS CULTURE SYSTEM - Wan Zaliha W.S.; Nurul Azilla M. (UPT Penerbitan Universitas Jember, 2017)
Black ginger (Kaempferia parviflora Wall. Ex. Baker) is herbaceous plant belonging to theZingiberaceae family and famously used in treating metabolic ailments, increasing vitality tohuman body, and relief gastrointestinal disorder. Recently, Black ginger has increasedattention from many researchers to identify their medicinal value to treat diseases. However, agronomic aspect particularly from growth and yield performances of black gingeris still lacking. Thus, a greenhouse experiment was conducted to determine the effects ofdifferent types of biochar substrates and rates on growth and yield performances of blackginger as an alternative planting method to replace soil cultivation method. By usingfertigation system as an adoption of soilless culture system, basic growth media werecombined with different types of biochar substrates and rates which treatments appliedwere: i) cocopeat (CP) (control, 4kg), ii) CP (3.8kg) with 200g rice husk biochar (RH), iii) CP(3.6kg) with 400g RH, iv) CP (3.4kg) with 600g RH, v) CP (3.8kg) with 200g palm kernel shellbiochar (PKS), vi) CP (3.6kg) with 400g PKS, vii) CP (3.4kg) with 600g PKS, viii) CP (3.8kg)with 200g sugarcane baggase biochar (SB), ix) CP (3.6kg) with 400g SB, x) CP (3.4kg) with600g SB, xi) CP (3.8kg) with 200g coconut shell biochar (CS), xii) CP (3.6kg) with 400g CS,and xiii) CP (3.4kg) with 600g CS. The experiment was arranged in a Randomized CompleteBlock Design (RCBD) with two factors and three replications. As expected, biochar haspromising effects on the growth and yields of black ginger. CPSB-black ginger with 600g ofbiochar had high and comparable value for number of leaves, plant height, plant per rhizome,total fresh weight, fresh and dry weight (leaves, rhizomes, and roots), leaf area, and leaf areaindex (LAI). Thus, CPSB combination with 600g rates of biochar could be suggested aseffective growing media for ginger cultivated in fertigation system.